Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences